Spoken grammar awareness raising: Does it affect the listening ability of Iranian EFL learners? - Rashtchi, Mojgan (Zakład Filologii Angielskiej: Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2011)
Advances in spoken corpora analysis have brought about new insights into language pedagogy and have led to an awareness of the characteristics of spoken language. Current findings have shown that grammar of spoken language is different from written language. However, most listening and speaking materials are concocted based on written grammar and lack core spoken language features. The aim of the present study was to explore the question whether awareness of spoken grammar features could affect learners’ comprehension of real-life conversations. To this end, 45 university students in two intact classes participated in a listening course employing corpus-based materials. The instruction of the spoken grammar features to the experimental group was done overtly through awareness raising tasks, whereas the control group, though exposed to the same materials, was not provided with such tasks for learning the features. The results of the independent samples t tests revealed that the learners in the experimental group comprehended everyday conversations much better than those in the control group. Additionally, the highly positive views of spoken grammar held by the learners, which was elicited by means of a retrospective questionnaire, were generally comparable to those reported in the literature.
Keywords: Corpus-based materials; Corpus linguistics; Real-life listening skills; Spoken grammar